DIGITAL TRANSFORMATION AND THE POTENTIAL FOR LABOR MARKET RESPONSE IN IRAQ (World Economics and Finance Bulletin, 2024)
The rapid technological booms that the world has witnessed since the 1990s have produced an era of radical changes and harbingers of the emergence of information and communications technology, artificial intelligence, the Internet of Things, and others. These profound transformations are driven by a revolution of technologies in several fields, that have cast their shadows in the reshaping the economic system, and the accompanying effects. Clear and evident in labor markets, which were coupled with unprecedented developments, especially in the areas of harnessing technology to expand the scope of services, and became the driving force for bringing about structural changes in countries' economies and individuals' lifestyles and relationships. The research aims to investigate the foundations of the digital economy and the sustainability of the competitiveness of the labor market in Iraq, allowing for the building of a workforce with digital technological skills that respond to new employment requirements, through the hypothesis that stipulates the adoption of a package of macro policies to mitigate the severity of the repercussions of the digital divide on the structure of the labor market in Iraq . The research reached a number of conclusions, which serve as a reflection of how the digital revolution has transformed the labor market and how universities can support students in order to enhance their employability, as well as recommendations that highlighted the need to improve the efficiency of the education system and ensure a balance between the outcomes of the educational process and the requirements of the new labor market. To prepare cadres who are aware of future digital trends, have the necessary skills, and are better prepared to comply with the conditions of these jobs